ANALISIS PERILAKU SEKSUAL PADA REMAJA DIFABEL DI SLB NEGERI PEMBINA PEKANBARU - Purnama " Pardede; Ari Pristiana Dewi; Juniar " Ernawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study aims to know the analysis of adolescents sexual behavior with disabilities in SLB Negeri Pembina Pekanbaru. Sexual behavior is behavior that is driven by sexual desire, both with the opposite sex or the same sex. Adolescents are individuals who were in the period of transition from childhood into adulthood, beginning around 10 years old to 13 years old and ended between the ages of 18 years old to 22 years old, and is characterized with a very rapid development from physical, psychological and sosial aspects. While disability is a defeciency that causes imperfect due to accident or other which causes the limitations on himself/ herself physically. This research uses quantitative approach with descriptive methods. The subject selection tecnique used total sampling that is 50 students. Interview by using picture is used to collect the data. The results of this study indicates the form of risky sexual behaviors such as kissing lips 12 students (24%) and palpating the sensitive body 8 students (16%). While unrisky behavior such as holding hand 36 students (72%), kissing cheek 23 students (46%), cuddle 28 students (56%) and masturbation 21 students (42%). The recomendation in this study is a practical action that can be adapted by parents or teachers to provide sex education for disabilities adolescents. Keywords : disabilities, sexual behavior and adolescents